Differences in Symptom Presentation in Women and Men with Confirmed Lower Limb Peripheral Artery Disease: A Systematic Review and Meta-Analysis. (April 2022) - Porras, Cindy P.; Bots, Michiel L.; Teraa, Martin; van Doorn, Sander; Vernooij, Robin W.M.
Abstract : Objective: To evaluate the differences in symptoms between men and women that present with lower limb peripheral artery disease (PAD). Data Sources: Systematic review and meta-analysis using PubMed, EMBASE, and the Cochrane Library. Review Methods: A systematic search of the literature to identify studies that examined PAD and its symptoms using PubMed, EMBASE, and the Cochrane Library, which were screened in duplicate by two reviewers. Information on study design, source of data, population characteristics, and outcomes of interest was extracted and used the Newcastle–Ottawa Scale and Cochrane risk of bias tool. Quality of evidence was rated using the GRADE methodology. Estimates of relative effects were pooled to generate pooled odds ratios (OR) and their 95% confidence interval (CI) using a random effects model. Results: Thirteen cross sectional studies, six cohorts, one case control, and one randomised clinical trial, reporting on 1 929 966 patients with confirmed PAD (established by clinical history, clinical examination, and/or ankle brachial index, or further tests) were included. Women presented less often with intermittent claudication than men (25.9% vs. 30.2%) OR 0.78 (95% CI 0.72 – 0.84, very low quality of evidence), while rest pain and atypical leg symptoms were more prevalent in women (12.8% vs. 9.2%) OR 1.40 (95% CI 1.22 – 1.60, very low quality of evidence) and (22.8% vs. 19.8%) OR 1.18 (95% CI 0.96 – 1.45, very low quality of evidence), respectively. Conclusion: Women with PAD more often present with rest pain, while their prevalence of intermittent claudication is lower. They also tend to present more often with atypical leg symptoms. This study underlines that PAD symptom presentation differs between the sexes. Therefore, clinicians and researchers should not consider men and women as a single population and report their data separately.